2019
DOI: 10.15294/edaj.v8i2.27237
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Leading Sector and Cluster Analysis of Regencies in Kalimantan

Abstract: To achieve the purpose of regional economic development, there is a need for development policy that is based on the characteristics of the region. Kalimantan is the centre of development in Eastern Indonesia which has strategic position for cooperation region. This study aimed to identify the potential leading sectors to develop and determine the regencies grouping and the characteristics of each group based on welfare indicators. The secondary data were collected from socio-economic data of 56 regencies duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Klassen Typology analysis is a combination of location share analysis tool or Location Quotient (LQ) with Growth Ratio Model (MRP) (Darma Putra & Yuli Pratiwi, 2019). Klassen typology can be used through two approaches: sectoral and regional.…”
Section: Methodsmentioning
confidence: 99%
“…Klassen Typology analysis is a combination of location share analysis tool or Location Quotient (LQ) with Growth Ratio Model (MRP) (Darma Putra & Yuli Pratiwi, 2019). Klassen typology can be used through two approaches: sectoral and regional.…”
Section: Methodsmentioning
confidence: 99%
“…The technique used to identify the contribution of an economic sector to the economy and its prospects involves a combined analysis of static and dynamic Location Quotient (LQ), Shift-Share, and Growth Ratio Model (MRP) (Putra & Pratiwi, 2019). This method has been employed in studies aiming to identify the leading sectors in a specific region and to develop future economic strategies to enhance competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have confirmed that examining a particular sector, such as agriculture and plantation [5,6], aquaculture [7], and livestock [8], could reflect the condition of the leading sectors and provide the basis for designing regional development. Scrutinizing and determining the leading sector is crucial in focusing and prioritizing the direction of development in regions with relatively limited resources [9][10][11]. In addition, Sukamara has seen a gradual increase in its economic sector, which influences the quality of its population.…”
Section: Introductionmentioning
confidence: 99%